ANALISIS PERAN GURU DALAM MENINGKATKAN LITERASI MEMBACA SD/MI: SYSTEMATIC LITERATURE REVIEW - Nayla Natasya; Ghina Rahma Tina; Nadilla Maharani; Anita Syuhada (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of teachers in improving reading literacy within the primary education demographic (elementary/Islamic primary schools). The employed methodology is a Systematic Literature Review (SLR), adhering to PRISMA guidelines. Information was gathered from Google Scholar utilizing relevant keywords. The initial search resulted in 80 articles, which were then filtered according to predefined inclusion and exclusion criteria, resulting in 10 selected documents for review. The outcomes show that teachers play roles as facilitators, motivators, guides, innovators, implementers, evaluators, and classroom managers. The strategies applied include school literacy programs, the use of illustrated storybooks, and the creation of a supportive literacy environment. All studies indicate improvements in reading skills, reading interest, and students’ comprehension. Therefore, optimizing the professional responsibilities of educators play a crucial part in enhancing the reading proficiency of elementary school students.